Ice Cover and Extreme Events Determine Dissolved Oxygen in a Placid Mountain Lake. Issue 9 (28th August 2020) - Flaim, G.; Andreis, D.; Piccolroaz, S.; Obertegger, U.
Abstract: A decrease in hypolimnetic dissolved oxygen (DO) is a commonly seen effect of climate change. However, in oligotrophic Lake Tovel (Italy), a deep mountain lake, annual mean DO (% saturation) has increased from near anoxia to >20% in the bottom layer (35–39 m). We analyzed long‐term patterns of DO (1937–2019) using different methods (correlation and trend analysis, identification of extreme events) to link DO to drivers and indices of mixing. While spring mixing remained temporally limited, later ice‐in (5.1 days decade −1 ) and the positive relationship between ice‐in and DO the following year evidenced autumn mixing as the main driver for hypolimnetic DO increase. Extreme meteorological events also replenished hypolimnetic DO. Using DO and conductivity (1995–2019), we identified 14 deep mixing events with hypolimnetic DO > 40%. Density‐based indices (Schmidt stability, relative thermal resistance, Lake Number, and Wedderburn Number) only partially captured these events that were related to snowmelt, flooding, and cold spells during spring and autumn, with a carryover effect sometimes lasting >1 year. Recently, annual mean DO in the upper layer decreased beyond temperature‐dependent solubility. This decrease was not comprehensively confirmed by statistical tests but was possibly linked to atmospheric stilling. We suggest that Lake Tovel's shift from meromixis to dimixis was driven by climate warming (i.e., increasing air temperature 0.6°C decade −1 ) that delayed ice‐in and increased autumn mixing. Our work underlines the vulnerability of mountain lakes and their different response to climate change with respect to more studied lowland lakes. Plain Language Summary: Dissolved oxygen is fundamental for aquatic life. Lake Tovel (Brenta Dolomites, Italy) has a long history of limnological studies starting in the 1930s; therefore, we can study oxygen's long‐term evolution. Contrary to most temperate lakes, dissolved oxygen is increasing in the deep layers of Lake Tovel since the 1990s. We linked this to later ice‐in: as a consequence of climate change, Lake Tovel has lost almost 3 weeks of ice cover since the mid‐1980s. This loss (5.1 days decade −1 ) in ice‐in is much steeper than in lowland lakes. Because dissolved oxygen is replenished in lakes by mixing, a longer ice‐free period means more time to mix, with oxygen reaching deeper layers. Extreme events such as heavy snowmelt, flooding, and cold spells during spring and autumn also increased mixing with effects often lasting over a year. However, in the last decade, we are beginning to see a decrease in dissolved oxygen at the surface, probably because of less wind. Years with little snow also tend to coincide with lower concentrations of dissolved oxygen in the deep layers. Changes in air temperatures, precipitation, and wind will determine the evolution of dissolved oxygen in Lake Tovel, a sentinel mid‐altitude lake for climate change. Key Points: Contrary to most temperate lakes, climate change has increased deep mixing in Lake Tovel, shifting the lake from meromictic to dimictic Delayed ice‐in in mountain lakes is occurring at a steeper rate than in most lowland lakes Dissolved oxygen and conductivity can indicate deep mixing events not always indicated by density‐based mixing indices